Nutrient density and the collaborative impact of exogenous enzyme blend on the performance of broiler chicken - Jun Young Mun; Habeeb Tajudeen; Sang Hun Ha; Jun Hyung Lee; Anushka Lokhande; Santosh Laxman Ingale; Jin Soo Kim; Min Ju Kim (Animal Bioscience)
Objective This study evaluates the collaborative effect of exogenous enzyme blend and dietary nutrient density on the performance of broiler chicken. Methods A total of 600 Ross 308 broiler chickens with same average initial body weight were randomly assigned to 5 treatments. Each treatment contained 8 replicates, and 15 birds per replicate. The diets included a control (CON) starter/finisher (S/F) diet with metabolizable energy (ME) 3,100/3,200 in Kcal/kg and crude protein (CP) content 22.0.0/20.00 in % as (S/F 3,100/3,200 Kcal/kg + CP [22.00/20.00]%), S/F with ME 3,060/3,150 Kcal/kg + CP (21.50/19.50)% with and without the exogenous enzyme blend as (S/F 3,060/3,150 Kcal/kg + [21.50/19.50]% with, and without the exogenous enzyme blend), and lastly, S/F with ME 3,010/3,100 Kcal/kg + CP (21.50/19.50)% with, and without the exogenous enzyme blend as (S/F 3,010/3,100 Kcal/kg + [21.50/19.50]% with, and without the exogenous enzyme blend). The impact of the treatments was tested on growth performance, nutrient digestibility, blood metabolites, intestinal microflora, and morphology of broiler chicken. Results The inclusion of exogenous enzyme blend in the nutrient-deficient diet S/F 3,060/3,150 + 21.50/19.50 increased (p<0.05) broilers body weight, feed conversion ratio, nutrient digestibility of CP, gross energy, phosphorus, and blood phosphorus, with tendency (p<0.10) of higher dry matter. The treatment also showed lower (p<0.05) total anaerobic bacteria, coliform, and higher (p<0.05) villus height (VH) in the jejunum, with tendencies (p<0.10) of higher lactobacillus in the ileum and caecum, and higher tendency (p<0.10) of VH in duodenum and ileum. Conclusion We concluded that the improved performance could be attributed to the potency of S/F 3,060/3,150 + 21.50/19.50 supplemented with 0.05% of the multienzyme to reduce the level of potential pathogenic bacteria with an increased level of positive bacteria, which in turn creates an enabling intestinal villi structure in broiler chicken.